The Impact of Physical Activity on Metabolic, Hormonal, and Psychological Profiles in Women with Polycystic Ovary Syndrome (PCOS): A Review of Current Evidence. - Frączek, Julia; Górka, Piotr; Tymińska, Paulina; Borówka, Karolina`; Kądziołka, Witold; Domagała, Szymon; Kawka, Natalia (Journal of Education, Health and Sport, 2026)
Background. Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder significantly impacting metabolic and psychological well-being. Physical activity is a cornerstone of non-pharmacological therapy, improving insulin sensitivity, lipid profiles, and body composition. Aim. This review aims to synthesize current evidence regarding the role of physical activity in PCOS management, focusing on cardiometabolic parameters, mental health, and reproductive functions. Material and Methods. An analysis of literature, including meta-analyses and systematic reviews, was conducted to evaluate the impact of various exercise modalities and "dosage" on patient health. Results and Discussion. Regular exercise significantly improves fasting glucose, cholesterol, and blood pressure while reducing inflammatory markers. High-Intensity Interval Training (HIIT) is more effective in reducing hyperandrogenism and visceral adiposity than moderate-intensity exercise. Physical activity alleviates anxiety and depression, though psychological barriers like negative body image may hinder adherence. While exercise promotes ovulation restoration (in up to 50% of patients), data remain heterogeneous. A research gap exists regarding PCOS in women with a normal BMI. Conclusions. Physical activity is a fundamental component of PCOS therapy, improving insulin sensitivity and ovulatory function independently of weight loss. Greatest efficacy is observed in high-intensity programs (min. 150 minutes/week). Success depends on individualized training and systemic psychological support. Further standardized research is needed to refine recommendations for different PCOS phenotypes.